Integrating Landscape Of Organizational Commitment Among Teachers In Indigeneous Primary Schools In Malaysia - MOKHTAR, NOORSURAYA MOHD; MOKHTAR, NOORSURAYA MOHD; HARUN, NORLAILI; AZMI, NOR FARHANA MOHD; MUSA, NOOR DALILA (The journal of contemporary issues in business and government, 2021)
Purpose of the study: This study focused on job satisfaction and organizational commitment among teachers who are teaching the indigenous students in the Pahang state. The purpose of this study was to identify the relationship between job satisfaction and organizational commitment among the teachers and to find out which dimension in job satisfaction scored the highest factors in fulfilling organizational commitment. Methodology: This is a correlational study adopting a quantitative approach in data analysis. A questionnaire on organizational commitment was adapted from Meyer and Allen (1990) while job satisfaction dimension was adapted from Spector (1985). The questionnaires were distributed to 51 respondents from 3 indigenous schools in Pahang. This study used purposive sampling technique and data were analysed using SPSS version 25. Main Findings: Findings showed a significant relationship between job satisfaction and organizational commitment among the teachers. The result showed that promotion opportunities were the element of job satisfaction that has the highest influence towards organizational commitment, meanwhile supervision has the factors lowest influence to organizational commitment. Applications of this study: This study is beneficial to the Pahang State Education Department in providing guidelines on how to increase organizational commitment among teachers in indigenous schools. Besides that, this study also benefits the school management as it offers a guideline for them to improve performance appraisal. The findings can also help future researchers by providing better understanding of the connection between job satisfaction and organizational commitment. Novelty/Originality of this study: Although literature pertaining to job satisfaction and organizational commitment has often been discussed internationally, there is a scarcity of investigation on the issue in the Malaysian context, explicitly in the topic related to indigenous school teachers. Hence, this study is trying to fill this gap.